UJI STABILITAS DAN UJI HEDONIK MASKER GEL PEEL-OFF EKSTRAK DAUN BINAHONG (Anredera cordifolia (Ten.) Steenis) DENGAN VARIAN KONSENTRASI POLIVINIL ALKOHOL (PVA) SEBAGAI FILMING AGENT - Tri Puji Lestari; Anisa Riana Putri; Ida Kristianingsih; Evi kurniawati; Fita Sari (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2022)
Research on the Formulation Physical Stability Test and hedonic test of the peel-off gel mask of binahong Leaf Extract has been conducted. This study aims to determine the best formula of the binahong Leaf Extract peel-off gel mask preparation with PVA as a filming agent. The steps of the procedure in this research include plant determination, sample preparation, making binahong leaves simplicia, making binahong leaves extract, formulation of peel off gel mask evaluation of physical properties, stability test, irritation test and hedonic test. Formulation of binahong Leaf Extract peel-off gel mask were carried out in three formulas with various variations of PVA concentrations of 5%, 5,5%, and 6%. The results of the physical properties test shows that peel-off extract masks of binahong leaves with different concentration variations differ in organoleptic, ph test, and drying time test a statistical data analysis. Based on the results of the stability test using the cycling test method with temperature ± 4̊ C and ± 40̊ C over the course of six cycles. he most stable results of existing tests are F2 and F3 showed no significant differences in each evaluation. Test irritation suggests that the gel peel-off mask was not irritating. From the hedonic test results, panelists prefer F3 compared to other formulas.